2000
DOI: 10.1086/309130
|View full text |Cite
|
Sign up to set email alerts
|

The Properties of Molecular Hydrogen toward the Orion Belt Stars from Observations by the Interstellar Medium Absorption Profile Spectrograph

Abstract: Absorption features from the Lyman and Werner bands of interstellar molecular hydrogen were recorded by the Interstellar Medium Absorption

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 73 publications
2
14
0
Order By: Relevance
“…equations suggest a similar, roughly linear relationship for cm~2, as long as the local density is not too N(H 2 ) [ 1015 highÈas seems to be indicated by the data in Figure 27. Higher resolution far-UV spectra of absorption toward H 2 f, d, and v Ori obtained with IMAPS (Jenkins & Peimbert 1996 ;Jenkins et al 2000) indicate that the general Na IÈH 2 relationship shown in Figure 27 holds as well for each of several groups of components along those three lines of sight. Figure 26 shows similar behavior for N(K I) versus though only the higher column density regime is N(H 2 ), well sampled.…”
Section: I Versus K I and Na Imentioning
confidence: 85%
See 1 more Smart Citation
“…equations suggest a similar, roughly linear relationship for cm~2, as long as the local density is not too N(H 2 ) [ 1015 highÈas seems to be indicated by the data in Figure 27. Higher resolution far-UV spectra of absorption toward H 2 f, d, and v Ori obtained with IMAPS (Jenkins & Peimbert 1996 ;Jenkins et al 2000) indicate that the general Na IÈH 2 relationship shown in Figure 27 holds as well for each of several groups of components along those three lines of sight. Figure 26 shows similar behavior for N(K I) versus though only the higher column density regime is N(H 2 ), well sampled.…”
Section: I Versus K I and Na Imentioning
confidence: 85%
“…The values for d Ori, v Ori, and f Ori H 2 are from higher resolution spectra obtained with IMAPS (Jenkins & Peimbert 1996 ;Jenkins et al 2000). There are a number of sight lines for which has not been measured, but may well be signiÐcant, based on the available CH column densities H 2 and the generally tight relationship found by Danks, Federman, & Lambert (1984) (e.g., for AE Aur, s2 Ori, f1 N(CH)ÈN(H 2 ) Sco).…”
Section: Discussionmentioning
confidence: 99%
“…To arrive at a total column density for H 2 , we must make a special assumption about the distribution in different rotational states. If the rotational temperature T rot of the H 2 were as high as about 1000 K, about the largest value seen in the general interstellar medium (ISM ) of our Galaxy (Spitzer et al 1974;Savage et al 1977;Jenkins et al 2000b) and elsewhere (Levshakov et al 2002), the occupations of the J ¼ 1 and 3 levels would be about equal to each other and together they would comprise 62% of the total over all levels. Thus, for T rot % 1000 K, we expect that our upper limit for H 2 in all J levels would be about 1:7 ; 10 15 cm À2 .…”
Section: Molecular Hydrogenmentioning
confidence: 95%
“…Large f H2 will be found when the sight line is dominated by the cores of diffuse molecular clouds, but the actual f H2 cannot be determined for individual velocity components because the strong low-J lines of H 2 are generally broader than the typical velocity separations between those components (Morton 1975). Based on higher resolution spectra of H 2 in low-N(H 2 ) sight lines obtained with IMAPS (Jenkins et al 2000), on even higher resolution spectra of other atomic and molecular species that are well correlated with H 2 (e.g., Welty & Hobbs 2001), and on the bvalues inferred from higher-J H 2 lines (e.g., Jensen et al 2010), it is likely that multiple components are present for most of the sight lines in which H 2 is detected. The highest integrated values of f H2 in the FUSE survey of highly reddened sight lines are between 0.65 and 0.76 (Rachford et al 2002(Rachford et al , 2009, slightly higher than the highest values found for the typically less reddened sight lines observed with Copernicus (Savage et al 1977).…”
Section: Diffuse Atomic and Molecular Gasmentioning
confidence: 99%